Analysis of Road Flexible Pavement Using The Bina Marga Method on Road Area of Aituto – Ainaro (Km 89 + 000 To Km 112 + 000) Timor Leste - Agostinho Dahu Tefa Da Silva (Journal of World Conference (JWC), 2022)
The highway is one of the transportation infrastructure that is being used to support economic activities. However, often on the road there is damage to the pavement which makes the comfort of the rider disturbed. One of them is Jalan Aituto – Ainaro Timor – leste, this road is a connecting road from the district city to the village. The purpose of this study was to determine in planning the thickness of flexible pavement on the 1987 SKBI Component Analysis Method, the 2017 Highways Method and the Dimensions of Edge Channels. The method used is an unstructured observation method and data collection in the form of primary data about the condition of the area on the Aituto - Ainaro Timor - Leste Road and secondary data in the form of LHR data, CBR data, road geometric data and rainfall data. From the results of the analysis of the component analysis method, the surface layer uses Asphalt MS 340 with a thickness of AC-WC 5 cm AC-BC 5 cm, the upper foundation layer uses Aggregate Class A with a thickness of 20 cm, and the sub-base layer uses Aggregate Class B with a thickness of 10 cm. . Meanwhile, from the results of the 2017 Bina Marga analysis, it was obtained that the surface layer used AC - WC with a thickness of 4 cm and AC - BC with a thickness of 6 cm, the upper foundation layer used AC - Base with a thickness of 14 cm and the lower foundation layer used LPA class A with a thickness of 30 cm. . The shape of the edge channel is rectangular with the channel dimensions calculated from the calculation of the channel width 0.8 m, channel height 0.7 m and girder height 0.6 m. and sub-base layer using Aggregate Class B with a thickness of 10 cm. Meanwhile, from the results of the 2017 Bina Marga analysis, it was obtained that the surface layer used AC - WC with a thickness of 4 cm and AC - BC with a thickness of 6 cm, the upper foundation layer used AC - Base with a thickness of 14 cm and the lower foundation layer used LPA class A with a thickness of 30 cm. . The shape of the edge channel is rectangular with the channel dimensions calculated from the calculation of the channel width 0.8 m, channel height 0.7 m and girder height 0.6 m. and sub-base layer using Aggregate Class B with a thickness of 10 cm. Meanwhile, from the results of the 2017 Bina Marga analysis, it was obtained that the surface layer used AC - WC with a thickness of 4 cm and AC - BC with a thickness of 6 cm, the upper foundation layer used AC - Base with a thickness of 14 cm and the lower foundation layer used LPA class A with a thickness of 30 cm. . The shape of the edge channel is rectangular with the channel dimensions calculated from the calculation of the channel width 0.8 m, channel height 0.7 m and girder height 0.6 m.